Searching for meaning: The mediating role of work engagement in the relationship between meaningful work and turnover intention of Millennials - Siahaan, Ferdinan Leonardo; Gatari, Eka (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
The trend of employees leaving companies is highest in the millennial generation, and is expected to continue to increase year on year. This study aims to ascertain how the meaningfulness of work affects the intention to leave through the role of work engagement as a mediator in the millennial generation sample studied. The research was conducted on 446 millennial generation employees (aged 20-37) working in various types of companies in Indonesia, using the convenience sampling method. The instruments used in the research were the Work as Meaning Inventory, Utrecht Work Engagement Scale-9, and the Turnover Intention Scale. Based on the mediation analysis, work engagement significantly acts as a mediator in the relationship between the meaningfulness of work and the millennial generation’s intention to leave their company (= -0.071, SE = 0.012, LLCI = -0.094, ULCI = -0.047). It is hoped that the findings from the study will provide information for organizations on promoting meaningful work and work engagement and thus increasing the desire of millennial generation employees to stay longer in their company or organization.